Ecology, environment and evolutionary history influence genetic structure in five mammal species from the Italian Alps - Vernesi, Cristiano; Hoban, Sean M.; Pecchioli, Elena; Crestanello, Barbara; Bertorelle, Giorgio; Rosà, Roberto; Hauffe, Heidi C. (Biological Journal of the Linnean Society, 2016)
The identification and evaluation of the ecological and environmental factors shaping patterns of natural genetic variation are fundamental goals of population and conservation genetics. Many studies focus on factors affecting single species, but it is also important to test whether some influential biotic and abiotic factors are common drivers of genetic diversity across species, or if species or species groups are each affected by different forces; a multi-species analysis is necessary for this. Here we analysed the molecular variation from five mammal species (roe deer, red deer, chamois, mountain hare and European brown hare) at mtDNA and microsatellite loci from the eastern Italian Alps. We use phylogeographical and landscape-level analyses to test the relative influence of large-scale geographical history and contemporary environmental characteristics of the landscape on genetic diversity and differentiation. We found: (1) all study species except brown hare are strongly differentiated into two main groups, located west and east of a major river valley; (2) significant correlations between levels of within-population diversity at both mtDNA and microsatellite loci, and several landscape features such as alpine grassland, water courses and anthropized areas. We conclude that heterogeneous landscape has some influence on within-population diversity, but biogeographical history has probably had the stronger influence on current genetic patterns, despite an apparently large dispersal potential of certain species. However, our results for brown hare show that management actions such as stocking may alter these large-scale patterns. © 2015 The Linnean Society of London, Biological Journal of the Linnean Society, 2016, 117, 428–446.